2022
DOI: 10.1186/s12871-022-01603-x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol suppresses adipose-derived stem cell progression via PI3K/AKT-Wnt signaling pathway

Abstract: Adipose-derived stem cell (ADSC) transplantation has become a prospective way to treat cardiovascular diseases and skin traumas. Propofol, a short-acting intravenous anesthetic agent, plays an important role in the induction and maintenance of general anesthesia. In this study, we investigated the effects of propofol on ADSCs. The flow cytometry results showed that ADSCs were positive for CD29, CD44, and CD90 and negative for CD31, CD34, and CD45. The results of MTT and BrdU assays demonstrated that propofol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…We demonstrated that LMSCs with 25 µM propofol showed better proliferation patterns than the cells with 0, 50 and 100 µM propofol in this study. A previous study reported that propofol had negative effects on adipose-derived stem cell proliferation, migration ability, invasion ability and cell viability via phosphatidylinositol 3-kinase/protein kinase B and wingless-related integration site pathways (12). These pathways play an important role in the autocrine and paracrine functions of the cell membrane and cell proliferation activities (15,16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that LMSCs with 25 µM propofol showed better proliferation patterns than the cells with 0, 50 and 100 µM propofol in this study. A previous study reported that propofol had negative effects on adipose-derived stem cell proliferation, migration ability, invasion ability and cell viability via phosphatidylinositol 3-kinase/protein kinase B and wingless-related integration site pathways (12). These pathways play an important role in the autocrine and paracrine functions of the cell membrane and cell proliferation activities (15,16).…”
Section: Resultsmentioning
confidence: 99%
“…Propofol has significant effects on many different tissue-specific MSCs (8,9,12). When sevoflurane or propofol was administered to cultured bone marrow-derived MSCs, sevoflurane was shown to reduce cell viability at concentrations of 2.3% and 3%, while propofol had no effect (8).…”
Section: Discussionmentioning
confidence: 99%